Tourism system / Fazurawaty Abdul Ghany - Abdul Ghany, Fazurawaty (Faculty of Computer and Mathematical Sciences, 2005)
Due to the growing popularity and complexity of the Web, designing a web Site is becoming a complex and diflScult process that need to be supported by more powerful Web engineering methods. Today, an ever-increasing number of businesses have set up Web sites to publicize their products and services. However, careful planning and preparation is needed to achieve the intended purpose of this new information exchange channel. This project proposed a comprehensive framework for effective agent application development based on tiie researches done in internet. The framework regards Web application development based on Pro-Web as a special type of software development. On the onset of this project, the tourist's wishes and preferences are investigated. Next, Uterature review, methodology, design, analysis and findings as the tourism industry in Perak Darul Ridzuan are examined. For Web page design, both the fimctionality and usability of Web pages are thoroughly considered. The knowledge in this system is represented using rules, while the forward inference technique is used to make generalization of certain criterions. Based on this project, a preliminary implementation of a prototype, the experience gained from this work and future work are described and few conclusions are drawn. Experience from the trial of the system shows that the Tourism System is a costeffective technology in facilitating the development of tourism applications across the internet. Although the system is successfully implemented, there still weaknesses and other future works can enhance this system